Caffeine ingestion stimulates plasma carnitine clearance in humans. Issue 4 (17th February 2023) - Wall, Benjamin T.; Machin, David; Dunlop, Mandy V.; Stephens, Francis B.
Abstract: Increasing skeletal muscle carnitine content can manipulate fuel metabolism and improve exercise performance. Intravenous insulin infusion during hypercarnitinemia increases plasma carnitine clearance and Na + ‐dependent muscle carnitine accretion, likely via stimulating Na + /K + ATPase pump activity. We hypothesized that the ingestion of high‐dose caffeine, also known to stimulate Na + /K + ATPase activity, would stimulate plasma carnitine clearance during hypercarnitinemia in humans. In a randomized placebo‐controlled study, six healthy young adults (aged 24 ± 5 years, height 175 ± 8 cm, and weight 70 ± 13 kg) underwent three 5‐h laboratory visits involving the primed continuous intravenous infusion of l ‐carnitine (CARN and CARN + CAFF) or saline (CAFF) in parallel with ingestion of caffeine (CARN + CAFF and CAFF) or placebo (CARN) at 0, 2, 3, and 4 h. Regular blood samples were collected to determine concentrations of blood Na + and K +, and plasma carnitine and caffeine, concentrations. Caffeine ingestion (i.e., CAFF and CARN + CAFF conditions) and l ‐carnitine infusion (i.e., CARN and CARN + CAFF) elevated steady‐state plasma caffeine (to ~7 μg·mL −1 ) and carnitine (to ~400 μmol·L −1 ) concentrations, respectively, throughout the 5 h infusions. Plasma carnitine concentration was ~15% lower in CARN + CAFF compared with CARN during the final 90 min of the infusion (at 210 min, 356 ± 96 vs. 412 ± 94 μmol·L −1 ; p  = 0.0080: at 240 min, 350 ± 91 vs. 406 ± 102 μmol·L −1 ; p  = 0.0079: and at 300 min, 357 ± 91 vs. 413 ± 110 μmol·L −1 ; p  = 0.0073, respectively). Blood Na + concentrations were greater in CAFF and CARN + CAFF compared with CARN. Ingestion of high‐dose caffeine stimulates plasma carnitine clearance during hypercarnitinemia, likely via increased Na + /K + ATPase activity. Carnitine co‐ingestion with caffeine may represent a novel muscle carnitine loading strategy in humans, and therefore manipulate skeletal muscle fuel metabolism and improve exercise performance.